Development of a rotary thermomagnetic motor for thermal energy conversion. - Ferreira, Lucas Diego Rodrigues (2018)
Thermomagnetic motors can represent an alternative for the conversion of heat into mechanical energy, limited by the critical transition temperature (TC) of the used magnetic materials. Thus, by using materials with a TC close to room temperature, the energy available in the form of low-grade heat sources can be converted into useful mechanical work. This thesis proposes the development of a thermomagnetic motor to be operated with heat sources at temperatures in the range from 343 to 353 K, and a heat sink at room temperature, using water as the heat transfer fluid, presenting a novel approach to the construction of thermomagnetic devices. The design of this thermomagnetic motor was developed with the intent of producing a rotary movement, working similarly to an electric stepper motor, where instead of the electromagnetic coils being activated by an electric current, plates of a magnetic material change their magnetization state, due to a change in their temperature caused by the heat transfer with the heat transfer fluid. The analysis of the thermomagnetic motor proposed was done with the adoption of an integrated approach of numerical simulation and experimental validation. The evaluation of the motor is divided into the three main physical phenomena it encompasses: the magnetic field source, the heat transfer processes involved in the change of temperature of the magnetic material, and the system dynamics and power production. Each of these systems was modeled using computational tools. These models were then validated according to the data measured, obtained from a test stand of an idealized thermomagnetic motor, and for a rotary thermomagnetic motor. This methodology allowed a more comprehensive understanding of the critical working principles of the motor developed, and with that a fast advancement of the technology through a validated computational model. The computational models helped to identify the critical components to be improved in the development of these motors. These parameters can be guidelines for the design of thermomagnetic motors. One of the ways identified to produce a significant performance improvement, in the simulations, was the adoption of a control strategy that promotes the regeneration of heat in the plates of magnetic material, through which an improvement in the efficiency of 2.7 times could be achieved.